The response of soil eukaryotic microbial communities to afforestation in mountainous area of the Loess Plateau, Northern China. - Yida An; Lei Zhang; Suqing Li; Yuanyuan Zhang (PLoS ONE)
Soil microorganisms are integral to nutrient cycling, ecosystem functioning, and soil restoration. However, the information on the response of soil eukaryotic microbial communities to land-use transformations, particularly for afforestation, remains underexplored in the mountainous region of northwest Shanxi on the Loess Plateau. The study based on high-throughput sequencing of 18S rRNA sequences, elucidated the impact of afforestation on soil eukaryotic microbial communities in this ecologically sensitive region. The findings indicated that afforestation significantly altered the composition of soil eukaryotic microbial communities. The dominant eukaryotic phyla were Streptophyta (16.8%-46.9%) and Ascomycota (20.5%-40.7%). At the genus level, Gymnoascus, Preussia, Mortierella, Chaetomium and Fusarium were biomarkers of soil eukaryotic microbes in farmland soil, while unidentified Streptophyta and Geopora were enriched in plantations soil. The result of non-metric multidimensional scaling (NMDS) analysis shows significant separation between eukaryotic microbial communities in farmland and plantation soils, which significantly correlated with soil temperature (T), nitrate nitrogen (NN) and available phosphorus (AP). These findings provided data support on regional ecological restoration assessments, highlighted the effect of soil physicochemical factors on the composition of soil eukaryotic microbial communities, and enhanced our understanding of the role of afforestation in modifying soil microbial ecosystems.